Forming Managerial Competence of the Future Manager of Educational Establishment as an Integral Component of His or Her Professionalism (by the Example of Khmelnytskyi Humanitarian-Pedagogical Academy) - Iryna Darmanska (Pedagogical Discourse, 2014)
The content of the curriculum of preparation of masters in the educational sphere of Khmelnytskyi Humanitarian-Pedagogical Academy has been analyzed in the article. On the basis of educational disciplines the author singled out components of managerial competence of the manager of educational establishment. The kinds of competences, which the manager should by all means possess, as a professional, have been determined. General scientific and professional-pedagogical competence, which make managerial subsystem, have been analyzed more detailed. On the basis of the mentioned competences the law competence, the competence of self-development, and self-education, competence of productive activity, andragogic, general sectoral, subject-methodological, diagnostic, educational and information-communicative competences have been analyzed. Each competence, mentioned in the article, is supported by the educational discipline, provided by the curriculum of preparation of masters on speciality “Management of Educational Establishment» (specialization “Manager of Institution, Establishment, Organization in the Sphere of Education and Industrial Training»). The necessity of inclusions of the mentioned disciplines into the plan of the future managers’ preparation, which will allow forming of managerial competence as an integral component of professionalism of the manager of educational establishment, has been reviewed.